MEASURING THE SOCIOECONOMIC IMPACTS OF SUSTAINABLE TOURISM DEVELOPMENT - Biju Gopal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
To draw upon their experiences to assist in our internal dialogue and presentations, it’s important to say that sustainable tourism has an important place in dealing with global environmental, economic, and societal problems. The socioeconomic impacts of sustainable tourism development are reviewed and opportunities and challenges in measuring these impacts are examined. Key benefits of local well-being include employment generation, income distribution, community development, and preservation of cultural heritage. The problem persists: there are no standardized metrics for measuring sustainability, data collection problems in developing regions, and managing tradeoffs between sustainability goals. While tackling these challenges, innovations are occurring within the technological frameworks that are beginning to utilize Big Data, Artificial Intelligence, and smart tourism practices to measure impact and resource management. Research and practice in the future must focus on upgrading governance structures, promoting community participation, and enhancing the linkages between tourism development and United Nation's Sustainable Development Goals (SDG) for long-term inclusive benefits. Tourism will contribute to global sustainability by integrating innovative technologies and strong policy frameworks to enable more adaptive, data-driven decision-making.